2015
DOI: 10.1007/978-3-319-20376-8_14
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Awareness Programs on Information Security in Banks: The Roles of Protection Motivation and Monitoring

Abstract: Abstract. Our aim is to understand how information security awareness (ISA) programs affect the intention of employees for compliant information security behavior. We draw on Protection Motivation Theory (PMT) to uncover indirect influences of ISA programs, and seek to identify the extent to which intention translates into actual compliance is contingent on monitoring. Based on partial least squares structural equation modeling analysis of 183 survey responses consisting of German bank employees, we find stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…While one study [41] failed to meet the threshold for a weak effect, a funnel plot also indicated that it represented an outlier in the available data. Of the other studies, one reported a medium effect [5] and five reported a weak effect [6,13,27,28]. Overall, our investigation therefore indicates a weak positive reliable effect for response efficacy on BI.…”
Section: Protection Motivation Theorymentioning
confidence: 47%
See 2 more Smart Citations
“…While one study [41] failed to meet the threshold for a weak effect, a funnel plot also indicated that it represented an outlier in the available data. Of the other studies, one reported a medium effect [5] and five reported a weak effect [6,13,27,28]. Overall, our investigation therefore indicates a weak positive reliable effect for response efficacy on BI.…”
Section: Protection Motivation Theorymentioning
confidence: 47%
“…Self-efficacy. Three studies [5,13] investigating the effect of selfefficacy on BI could be found in the literature review. All three show small effects (0.190 ≤ β ≤ 0.296), drawing a relatively clear picture.…”
Section: Protection Motivation Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…In a general way, ISA programs and ISATs may generate a false sense of security, as taking part in ISA programs reduces perceptions of vulnerability, while the intentions for compliant security behavior are not affected [77]. Information and IT security awareness-raising measures and the evaluation of these measures are an indispensable part of today's information and knowledge society [65].…”
Section: Discussionmentioning
confidence: 99%
“…In the German banking sector, Bauer and Bernroider find strong empirical evidence showing the importance of ISA programs, protection motivation, and monitoring [4], while the findings of Fagade and Tryfonas suggest that security by compliance as a campaign to secure information assets in Nigerian financial institutions is a far-fetched approach [24]. This might relate to sociocultural influences on ISA.…”
Section: Kab: Knowledge Attitude Behaviormentioning
confidence: 99%